Latviskā izglītība Rietumvācijā (1944-1949) - Ozoliņa, Lidija (Latvijas Universitāte, 2006)
Bakalaura darba autore pētījusi un apskata latviskās izglītības organizēšanas apstākļus, procesus, tendences un norises latviešu bēgļu nometnēs Vācijā laika posmā no 1944.gada otrās puses līdz 1949.gada beigām. Latviskā izglītība Rietumu trimdā Vācijas periodā tika organizēta ar mērķi nezaudēt laiku, atrodoties ārpus Latvijas, lai bērni un jaunieši varētu turpināt un pabeigt kara darbības rezultātā pārtraukto izglītošanos dzimtenē, bet pieaugušie gūtu iespēju pārkvalificēties, un, atbilstoši apstākļiem atrastu peļņas darbu.

The author of the bachelor paper has studied and considered the conditions, processes, tendencies and progress of the organization of Latvian education at the time of Latvian refugees'camp in Germany during the period from 1944 to 1949. The Latvian education of Western exile of the German period was organized in order not to lose time being abroad and to give the chance to children and young people to continue and complete their education which was interruped by war operation at their home land. The other goal was to give grown - ups the opportunity to retrain gaing a new profession as well as to find a paidjob which corresponded to the cirstumcances.
Latvian Education in West Germany (1944-1949)
Keywords: Vēsture